Incidencia del Precio del Dólar Estadounidense en las Exportaciones de Café del Departamento del Tolima entre 2018-2022 (2024)
This work aims to analyze the impact of exchange rate appreciation or depreciation on coffee exports from the Tolima department during the period 2018-2022. The research was conducted using a quantitative and correlational approach supported by public statistical sources.